Unveiling of free carrier transport and ion migration in a 2D-3D perovskite mixture for stable optoelectronic devices - Nguyen, Bich Phuong; Youn, Sarah Su-O; Kim, Yeon Soo; Nguyen, Thuy Thi; Park, Ha Kyung; Kim, Gee Yeong; Jo, William (Royal Society of Chemistry, 2025)
Manipulating charge carrier recombination dynamics in mixed three-dimensional (3D) and two-dimensional (2D) perovskites is an effective approach to enhance performance and long-term stability in both solar cells and light-emitting diodes (LEDs). Due to high crystallinity and a low charge carrier recombination coefficient, photogenerated charge carriers in solar cells can effectively diffuse across the perovskite layer, while enhancing radiative recombination through charge carrier confinement can significantly improve electroluminescence efficiencies in LEDs. Further improvements in device efficiency and stability require a comprehensive understanding of charge carrier transport at the numerous interfaces between the different phases of 2D perovskites at both the micro- and nanoscale, as well as ion migration. In this study, we examine the carrier transport mechanism at the thin-surface 2D/bulk 3D perovskite interface and the dense-surface 2D/3D heterophase. The electrical properties and ion migration behavior were analyzed by examining the transition of the J-V characteristics in both vertical and lateral devices. We carefully analyzed the influence of nanostructures on charge transport using conductive atomic force microscopy (C-AFM) and Kelvin probe force microscopy (KPFM). The variation in the spatial response of the photocurrent and surface photovoltage across grains and grain boundaries with different phases of the 2D perovskite was carefully examined. These insights provide a pathway for optimizing the electrical properties and charge transport behavior of mixed perovskites, further positioning them as key materials for the development of efficient and stable optoelectronic devices.